Ultrastructure of granulated cells in the bile duct of reindeer - Sven Nikander; Timo Rahko (Rangifer, 1990)
The presence and ultrastructural characteristics of mast cells and globule leucocytes in bile ducts of the reindeer have not been previosly documentated. Tissue blocks of ductus bepaticus communis from six reindeer were processed by commonly used methods for TEM and examined with a JEOL JEM 100 S electron microscope. The present material originates from reindeer without clinical signs of parasites. However, several types of granulated cells were identifiable. The granules of connective tissue and subepithelial mast cells were small and mostly diffusely electron dense but also fine granular matrices were shown. The globules of intraepithelial globule leucocytes were fewer in number and distinctly larger than the granules of the mast cell. In addition there were noted intraepithelial granulated cells appearing similar to the neuroendocrinic cells reported in bovine bile ducts.